Unique observation method of temperature dependence of diatom floating by direct microscope - Ide, Yuki; Matsukawa, Yuji; Miyashiro, Daisuke; Mayama, Shigeki; Julius, Matthew L.; Umemura, Kazuo (Journal of microbiological methods, 2020)
Diatoms are one of the earth's major oxygen producers. For that reason, studying the floating phenomena of living diatom cells in water is an important research subject. Efficiency of photosynthesis of diatom cells may be heavily affected by their floating behavior. In our previous research, we devised a ‘tumbled’ microscope, a device created by tilting an inverted microscope (CKX53, OLYMPUS) by 90 degrees, due to which allowed observation with a sample stage perpendicular to the ground. When we observed a Petri dish filled with diatom cell suspension, the floating behavior of diatom cells were well visualized. Cyclotella meneghiniana was isolated and subcultured in bold modified basal freshwater nutrient solution liquid medium (B5282-500ML, Sigma-Aldrich) at 18 °C. Before the microscopic observation, cell suspension was cultured for two weeks after the final subculture. Observation was performed at room temperature, 30 °C, and 40 °C with a temperature sensor in the center of the chamber (inside). Observations were started as soon as the sample was installed. In a typical image obtained using the tumbled microscope, the diatom cells were found to move from the top to the bottom. In order to analyze floating velocity and trajectory, observation was continued for 35 min at room temperature, 30 °C, and 40 °C. Tracking analysis was carried out using the two-dimensional motion image measurement software Move-tr/2D. The average speed of 100 cells was 7.0 ± 4.3 μm/s at room temperature, 85.6 ± 31.9 μm/s at 30 °C and 470.1 ± 279.8 μm/s at 40 °C. In this study, we devised the unique observation to visualize the temperature dependence of diatom cells. •Visualize the floating phenomenon of diatom cells using a self-made glass chamber.•The environmental temperature of diatom can be arbitrarily changed using a temperature control heater.•This method is suitable for quantitative analysis of diatom floating phenomena.